Answer:
![\sf \text{The numbers are $(-14)/(3) $ and $(-7)/(3)$}](https://img.qammunity.org/2023/formulas/mathematics/college/h6sfayv8md73uxsq9jt9yg9alwh0t4szn0.png)
Explanation:
Let the numbers be x , y
Sum of two numers = -7
x + y = -7------------(I)
Two times the first number equals 4 the second number.
2x = 4y ----------(II)
Divide both sides by 2
![\sf (2x)/(2)=(4y)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/waudriw3fztwj3zxctb7y4tcwbzctt7wuy.png)
x = 2y
Subtitute x = 2y in equation (I)
2y + y = -7
3y = -7
y = -7/3
Plugin y = -7/3 in equation (II)
![\sf 2x = 4*(-7)/(3)\\\\2x = (-28)/(3)\\\\x =(-28)/(3*2)\\\\x = (-14)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/6obt2jb46wr2bfqe3a619vlk0oxd8up757.png)